ANALYSIS SUPPLY CHAIN MANAGEMENT OF TOMATO BEEF AGRIBUSSINESS (Case Studies in Tani Maju Group Dusun Junggo Kecamatan Bumiaji, Batu) - Triyasari, Sri Ratna; Muhaimin, Abdul Wahib; Koestiono, Djoko (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2015)
Main strength of agribusiness is the fulfillment of demand for agricultural products. However, this demand is often located in cities and industrial centers, whereas the production site of agribusiness is always far away from cities and industrial centers where the demand derives from. Indonesian farmers are lacking of competing ability, and therefore, it is hard to give better quality of supply and more punctuality of procurement. Punctuality is highly required by consumer and therefore, this research attempts to discuss punctuality. The objective of research is to analyze the performance of tomato beef supply chain management and the long-term relationship among the agencies of tomato beef supply chain management. To achieve this objective, research uses analysis methods of SCOR AHP and descriptive statistic. Result of research indicates that the performance of tomato beef supply chain management may be classified already as the good one but it can still be improved by establishing the main priority or the best solution alternative for supply chain management, which respectively is the making of long-term business contract. Therefore, long-term relationship among the agencies of tomato beef supply chain management will be stronger.